Effect of tillage systems and vine orientation on yield of sweet potato (Ipomoea batatas L.) - Chagonda, Ignatius; Mapfeka, R. F.; Chitata, T. (Scientific Research Publishing, 2016)
In Zimbabwe sweet potato (Ipomoea batatas L.) production is practiced under different tillage systems with varying vine orientations, which contribute to variable yields. Limited research on yield loss due to these different practices is available despite that the majority of farmers are growing sweet potatoes to sustain their livelihoods. A field study was carried out at Midlands State University in the 2013/14 rainy season, to determine the effect of tillage systems and vine orientation on yield of sweet potato. A 2 × 3 factorial treatment structure in a randomized complete block design (RCBD), with three replications was used. Tillage systems had two factors (ridge and mound) and three vine orientations were used (horizontal, fold and loop). Data on storage root length, storage root diameter and storage root weight was subjected to Analysis of Variance (ANOVA) at 5% significance level. There was no interaction (p < 0.05) between tillage systems and vine orientations on storage root diameter, storage root length and storage root yield. The horizontal vine orientation gave statistically significant (p < 0.05) storage roots diameter of width 405mm. Conversely the loop vine orientation had statistically the least (316 mm) storage root diameter. Horizontal vine orientation had significantly (p < 0.05) wider storage roots than the loop vine orientation. The ridge recorded longer (134.2 mm) mean storage root length, while those from mounds had shorter (115.9 mm) root length. The loop and the horizontal vine orientations recorded statistically the highest (35.5 t/ha and 34.8 t/ha respectively) sweet potato storage root yield. On the other hand, the fold vine orientation obtained significantly the lowest (28.7 t/ha) storage root yield. The research concluded that the horizontal and fold vine orientations had the widest storage root diameter and the ridge had longer storage root lengths. The loop and horizontal vine orientations are recommended in sweet potato production if high yields are to be achieved.